Survey of the solicitors' profession, 1989 - Chambers, G. (UK Data Service, 1993)
To obtain a profile of the structure, organisation and staffing of solicitors' firms; to describe the types of legal and non-legal work carried out by solicitors; to investigate the social background of solicitors including career history and educational qualifications; to explore solicitors' attitudes on a variety of professional issues.